Pelatihan Tata Kelola dan Manajemen yang Baik bagi Badan Usaha Milik Desa (BUMDes) di Kabupaten Banyuwangi - Izzato Millati; Siti Nur Hilmin; Erina Sudaryati; Sandra Sukma Embuningtiyas (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
Good governance and management Training activities for BUMDes in Banyuwangi Regency 2022 are organized by lecturers and also students of the SIKIA Accounting Study Program, Airlangga University. The form of this program is community service in the form of providing material regarding BUMDes Financial Management Governance, followed by mentoring activities afterwards. The speakers for this activity were representatives of the Community and Village Empowerment Service, lecturers of the PSDKU Accounting Study Program, Airlangga University, Banyuwangi, and alumni of the PSDKU Accounting Study Program, Airlangga University, Banyuwangi. This activity aims to help the community, especially representatives from BUMDES and several sub-districts in Banyuwangi, understand the correct procedures for managing financial management. Apart from that, assistance is also held so that the community can directly practice and ask questions later during the assistance, with the hope that the community really understands how to manage finances properly and correctly. Apart from that, assistance is also held so that the community can directly practice and ask questions later during the assistance, with the hope that the community really understands how to manage finances properly and correctly.